Tanshinone IIA ameliorates non-alcoholic fatty liver disease through targeting peroxisome proliferator-activated receptor gamma and toll-like receptor 4 - Huang, Lu (J Int Med Res, 2019)
OBJECTIVE: To investigate the cellular mechanisms of action of tanshinone IIA on the fatty liver disease induced by a high-fat diet in an animal model of non-alcoholic fatty liver disease (NAFLD). METHODS: Adult male Sprague Dawley rats were randomized into one of three groups: regular rat diet (CON group) for 4 months; high-fat diet (HFD group) for 4 months; HFD for 2 months followed by tanshinone IIA treatment plus HFD (TAN group) for a further 2 months. A range of physical and biochemical markers of lipid accumulation and fatty liver disease were measured and compared between the groups. RESULTS: Tanshinone IIA treatment significantly reduced fat accumulation in the liver and plasma lipid levels that had been increased by HFD. The toll-like receptor (TLR4)/nuclear factor kappa B (NF-κB) signalling pathway was silenced by tanshinone IIA treatment. Tumour necrosis factor-α and interleukin-6 were reduced by tanshinone IIA. Hepatocyte apoptosis was inhibited by tanshinone IIA. Tanshinone IIA upregulated peroxisome proliferator-activated receptor gamma (PPAR-γ), which resulted in an improvement in the oxidative status. CONCLUSION: Tanshinone IIA ameliorates NAFLD by targeting PPAR-γ and TLR4, resulting in decreased plasma lipids and oxidative stress, suggesting this strategy may form the basis of novel NAFLD therapies.